Anatomical variations and clinical significance of the pyramidalis muscle: A detailed morphometric analysis in cadaveric population - Pratyusha Challa; Ranzeetha D; Pavana Kumari KV; Lakkireddy Vasanthi; Srinidhi Kondepudi (Asian Journal of Medical Sciences, 2024)
Background: The pyramidalis muscle, often considered a minor muscle of the anterior abdominal wall, has variable presence and morphology across populations. Its clinical significance, particularly in surgical interventions involving the suprapubic region, necessitates a detailed understanding of its anatomical features. Aims and Objectives: This study aimed to assess the incidence, morphometric variations (length, width, and thickness), and clinical relevance of the pyramidalis muscle in the cadaveric population, offering insights that could enhance surgical outcomes in the suprapubic region. Materials and Methods: It conducted on 60 formalin-fixed cadavers from the Department of Anatomy at Guntur Medical College, Guntur, and Government Medical College, Ongole. This study utilized digital Vernier calipers and measuring tape for precise morphometric analysis. Parameters such as presence, number of bellies, length, width, thickness, and the Pyramidalis Pubo Umbilical Index were meticulously recorded. Results: The pyramidalis muscle was present in 83.3% of the cases, with 80% bilateral and 3.3% unilateral occurrences. The mean length was 66.2 mm on the right and 64.4 mm on the left. The width at the base averaged 23.4 mm (right) and 22.5 mm (left), with a consistent mean thickness of 4.1 mm on both sides. The Pyramidalis Pubo Umbilical Index was 39.82 (right) and 39.2 (left), indicating little variation between sides. Conclusion: The pyramidalis muscle exhibits a high incidence rate and specific morphometric characteristics in the cadaveric population. These findings underscore its potential impact on surgical approaches in the suprapubic area, providing valuable anatomical insights for healthcare professionals.